Sedimentation rate in Bera Lake and soil redistribution at its catchment using radioisotopes / Mohammadreza Gharibreza - Gharibreza, Mohammadreza (2012)
The Bera Lake is a lacustrine system and the largest natural lake in Malaysia. Assessment of literature review has highlighted a clear gap in the evaluation of environmental impacts of anthropogenic activities on the soil and water resources and sedimentary regime. Accordingly, determination of soil and nutrient redistribution in the catchment area, and sedimentation rates, nutrients fate and sediment quality assessment at Bera Lake using fallout 210Pb and 137Cs radioisotopes and sediment quality guidelines have been defined as aims of the present research. A comprehensive methodology was formulated to perform an effective literature review, innovation of core sampler, field surveying, detailed experimental measurements, mapping, and an advanced modeling. A wide range of models and a geo-referenced “GIS-ready” data set have supported the designed methodology. Application of fallout 137Cs inventories and proportional model provide the mean of soil erosion of 914±345, 117±36, and 70±35, t h-1 y-1 in cleared lands, immature and mature oil palm plantations. A negative correlation between nutrient contents and the extent of land development was established in the study area Stratigraphic dates based on records of fallout 137Cs and 210Pb supply rates to Bera Lake sediment columns have remained relatively constant. As a result, the CRS model is applied for geochronology of Bera Lake sediments. The estimated maximum 210Pb flux and sedimentation rate were 159±2 Bq cm-2 y-1 and 2.56 cm y-1, respectively in the semi-closed area at the north of Bera Lake. The mean pre-1950 sedimentation rate was 0.08±0.02 g cm-2 y-1 (0.1±0.1cm y-1), which indicate a uniform accumulation trend prior to anthropogenic activities. Sedimentation rates raised were by 10 times since 1972 following deforestation. Accordingly, a white sandy mud layer was deposited between 1972 and 1993 at the south, middle, and the north of Bera Lake at mean rates of 0.48±0.48, 0.54±1.2 and 0.17±0.12 g cm-2 y-1. Establishment of mature oil palm plantations are promoting biomass productivity to 1.5 mil y-1, dominates organic matters in run-off and accumulation of organic-rich deposits at mean rate of 0.2±0.1 g cm-2 y-1 (1.3 cm y-1) at the uppermost layer of Bera Lake sediment sequence since 1994. Overall sedimentation rates in Bera Lake basin using 210Pb date and CRS model, fallout 137Cs and proportional model, and trap efficiency and sediment discharge values were 0.99, 1.025, and 1.11 cm y-1, respectively. Sediment quality guidelines have shown that lake deposits severely polluted by As and the north part polluted by Fe. Besides, Bera Lake sediment profiles are moderately polluted by Cu, Cr, and Ni. A clear eutrophication in Bera Lake has occurred due to deforestation phases in the catchment area. To sum up, achievements have confidently approved capability of selected methods to achieve the research objective. Present study has remarkably contributed in knowledge due to formulation of the suitable method to estimate soil erosion in oil palm plantations in Malaysia, and sedimentation rates and reconstruction history of a natural lake, assessment of sediment quality and an integrated management plan for a sustainable land use and conservation of water and soil.